2004
DOI: 10.1038/oby.2004.242
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Accumulation as a Risk Factor for Prostate Cancer

Abstract: VON HAFE, PEDRO, FRANCISCO PINA, ANA PÉ REZ, MARGARIDA TAVARES, AND HENRIQUE BARROS. Visceral fat accumulation as a risk factor for prostate cancer. Obes Res. 2004;12:1930 -1935. Objective: No clear association between obesity or body fat distribution and prostate cancer has been shown. We investigated the relation between visceral fat accumulation as measured by computed tomography (CT) and the occurrence of prostate cancer. Research Methods and Procedures:We compared body fat distribution assessed by a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 67 publications
2
91
0
2
Order By: Relevance
“…Recent epidemiological studies have found that abdominal adiposity, in particular the presence of a large VAT compartment, is an important risk factor for cancer development and results in poor prognosis. [16][17][18][19][20] These findings suggest therefore that adipose tissue distribution may be an independent prognostic factor in patients treated curatively for localized prostate cancer. The prognostic significance of abdominal fat distribution in patients with prostate cancer treated with EBRT on Gleason score (GS), prostate-specific antigen (PSA) or clinical stage and outcomes, has not yet been studied.…”
Section: -14mentioning
confidence: 78%
“…Recent epidemiological studies have found that abdominal adiposity, in particular the presence of a large VAT compartment, is an important risk factor for cancer development and results in poor prognosis. [16][17][18][19][20] These findings suggest therefore that adipose tissue distribution may be an independent prognostic factor in patients treated curatively for localized prostate cancer. The prognostic significance of abdominal fat distribution in patients with prostate cancer treated with EBRT on Gleason score (GS), prostate-specific antigen (PSA) or clinical stage and outcomes, has not yet been studied.…”
Section: -14mentioning
confidence: 78%
“…There are contradictory results from several studies using body mass index (BMI) to evaluate adiposity. [24][25][26][27][28][29] However, studies using abdominal adiposity measurement, either by waist-to-hip ratio 30 or CT scan, 31 found an increased risk for PCa.…”
Section: Obesity and Pcamentioning
confidence: 99%
“…For example, several studies report that obesity is associated with the stage of cancer at detection, 11,12 and a metaanalysis from MacInnis and English estimated that each 5-unit increase in BMI was associated with an approximate 5% increase in the risk of developing advanced prostate cancer. 12 Furthermore, clinical prostate cancer risk has been associated with the metabolic syndrome, 13,14 centralized obesity, 15 leptin levels [16][17][18] and insulin resistance. 19,20 However, several studies report no evidence of an association, [21][22][23][24][25][26][27] while others report that BMI is associated with reduced risk of prostate cancer, particularly low-grade tumors.…”
Section: Introductionmentioning
confidence: 99%